2004
DOI: 10.1111/j.1475-6773.2004.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness and Length of Inpatient Stay for Medicaid Recipients with AIDS

Abstract: Objective. To examine the associations between comorbid mental illness and length of hospital stays (LOS) among Medicaid beneficiaries with AIDS. Data Source and Collection/Study Setting. Merged 1992–1998 Medicaid claims and AIDS surveillance data obtained from the State of New Jersey for adults with ≥1 inpatient stay after an AIDS diagnosis from 1992 to 1996. Study Design. Observational study of 6,247 AIDS patients with 24,975 inpatient visits. Severe mental illness (SMI) and other less severe mental illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…This may then be compounded by short hospitalizations that do not adequately address the complicated nature of co-occurring substance abuse, medical and psychiatric illnesses these patients have. [24] Finally, without proper outpatient post-hospital aftercare that evaluates and treats these illnesses in the outpatient realm, it is quite possible that these problems will inevitably require additional hospitalizations. [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may then be compounded by short hospitalizations that do not adequately address the complicated nature of co-occurring substance abuse, medical and psychiatric illnesses these patients have. [24] Finally, without proper outpatient post-hospital aftercare that evaluates and treats these illnesses in the outpatient realm, it is quite possible that these problems will inevitably require additional hospitalizations. [42].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study in the HAART era found that individuals with AIDS and a history of SMI had similar length of inpatient medical hospital stays, compared to those with no mental illness history. [24] Although both studies noted that injection drug use (IDU) was associated with longer lengths of hospitalization, neither study investigated whether a co-occurring SMI diagnosis and a history of IDU was associated with increased utilization of inpatient medical admissions or longer lengths of stays.…”
Section: Introductionmentioning
confidence: 99%
“…(2008) found that even with retrospective approaches, the method used to identify mental illness influenced prevalence rates which would influence the measurement of outcomes. All retrospective studies considered in this review used the same method, secondary diagnostic codes, for identifying psychiatric comorbidity, except the study by Hoover et al. (2004), which also included psychiatric history and outpatient psychiatric treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Because administrative data does not contain CD4 cell counts, a biomarker of HIV disease severity, we used the presence or absence of an AIDS Defining Illness, determined by ICD-9 diagnostic codes, as a surrogate marker of disease severity. This has been used in other HIV studies using administrative claims data (Hoover et al, 2004). …”
Section: Methodsmentioning
confidence: 99%
“…(Hoover et al, 2004) Despite this there may still have been residual confounding. Second, entry into our cohort required two years of continuous…”
Section: Introductionmentioning
confidence: 99%